NUMERICAL INVESTIGATION OF THE SINGLE PHASE FORCED CONVECTION HEAT TRANSFER CHARACTERISTICS OF NANOFLUID FLOWING IN SMOOTH AND MICRO-FIN TUBES - Kayaci, Nurullah; Tabatabaei, Mahdi; Celen, Ali; Yildiz, Oguzhan; Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2013)
Forced convection flows of nanofluids containing of water with TiO2 nanoparticles in smooth and micro-fin tubes with constant wall temperature are studied numerically in this paper. A single-phase numerical model having three-dimensional equations is solved with either constant heat flux or temperature dependent properties to determine the hydrodynamics and thermal behaviors of the nanofluid flow by means of a CFD program for the water flow in a smooth tube and micro-fin tubes having various helix angles (0 degrees,18 degrees). An intensive literature review on the determination of the physical properties (k, mu, rho, C-p) of nanofluids is given in the paper. The numerical model is validated by means of a CFD program using the experimental smooth tube data as a case study and it is also solved in the CFD program for several micro-fin tubes as a simulation study. Velocity, temperature and pressure distributions are shown in the paper. Besides this, the values of experimental and numerical are compared with each other in terms of friction factors, shear stresses, convective heat transfer coefficients and pressure drops. Moreover, the effects of the presence of nanofluids and micro-fins in the inner surface of the test tube on the heat transfer characteristics are investigated in detail.
Keywords: EFFECTIVE THERMAL-CONDUCTIVITY; TRANSFER ENHANCEMENT; PRESSURE-DROP; THERMOPHYSICAL PROPERTIES; RHEOLOGICAL BEHAVIOR; VISCOSITY; TEMPERATURE; SUSPENSIONS; TRANSPORT; FRACTION; Engineering